Implementasi Integrated Light Out (ILO) Dalam Jaringan Virtual Private Network Pada PT. Alfar Teknologi Solusindo - Muhamad, Arief; Mulyani, Astriana; Sari, Eka Puspita (JURIKOM (Jurnal Riset Komputer), 2018)
PT. Alfar Teknologi Solusindo is engaged in the field of IT consultants whose fields of work include procurement of goods, hardware installation, and software, and after sales that must be maintained in order to be able to solve problems that occur in the Client, both clients in Jakarta and outside the Province DKI Jakarta because of course it has a need to be interconnected. Problems that often occur if there are problems outside Jakarta that require technicians to go to an area where more costs, time and peace are needed. To overcome the problems faced by PT Alfar Teknologi Solusindo he designed an Integrated Light Out Implementation in Virtual Private Network Networks at PT. Alfar Teknologi Solusindo. This implementation is expected to be able to monitor and be able to access directly to the server even though the server hardware is in a dead state or a blue screen remotely thereby reducing the costs incurred by the company.